Contemporary art from the Netherlands : [Tiong Ang...] : [exhibition, Stedelijk Van Abbemuseum, Eindhoven, February 14-April 13, 1998]. - Steevensz, Bert; Sütö, Wilma; van Ulzen, Patricia; Buravio, Maurice; van den Berg, Mariska; Vande Veire, Frank; Reijnders, Tineke; Berndes, Christiane; ter Braak, Lex; Seijdel, Jorinde; Van Abbemuseum, Eindhoven (Eindhoven : Stedelijk Van Abbemuseum, 1998)
Ang, Tiong ; Arink, Karin ; Atelier van Lieshout ; Baerveldt, Erzsébet ; Dijkstra, Rineke ; Eisinga, Jeroen ; Jolink, René ; Kinoshita, Suchan ; Koelewijn, Job ; Manders, Mark ; et al.
Contemporary Art from the Netherlands, Stedelijk Van Abbemuseum, Eindhoven, February 14 - April 13, 1998
kunstcatalogus
Keywords: Nederland